Autism and epilepsy: A population-based nationwide cohort study. (12th July 2016) - Sundelin, Heléne E.K.; Larsson, Henrik; Lichtenstein, Paul; Almqvist, Catarina; Hultman, Christina M.; Tomson, Torbjörn; Ludvigsson, Jonas F.
Abstract : Objective: To investigate the risk of autism spectrum disorder (ASD) in individuals with epilepsy and in their first-degree relatives to determine shared etiology. Methods: Through the Swedish Patient Register, we identified 85, 201 individuals with epilepsy, as well as all their siblings (n = 80, 511) and offspring (n = 98, 534). Each individual with epilepsy was compared with 5 controls, matched for age, sex, calendar period, and county, while siblings and offspring were compared with siblings and offspring of controls. We excluded siblings and offspring with epilepsy. Using Cox regression, we calculated hazard ratios (HRs) for future diagnosis of ASD. Logistic regression was applied to calculate odds ratios (ORs) for prior diagnosis of ASD. Results: During follow-up, 1, 381 (1.6%) individuals with epilepsy and 700 (0.2%) controls were diagnosed with ASD. Individuals with epilepsy were therefore at increased risk of future ASD (HR 10.49, 95% confidence interval [CI] 9.55–11.53), with the highest risk seen in individuals diagnosed with epilepsy in childhood. Both siblings (HR 1.62, 95% CI 1.43–1.83) and offspring (HR 1.64, 95% CI 1.46–1.84) of epilepsy patients were at increased risk of ASD. The risk in the offspring was particularly high in mothers with epilepsy (HR 1.91; 95% CI 1.63–2.23). Epilepsy was also associated with a prior diagnosis of ASD (OR 4.56, 95% CI 4.02–5.18). Conclusions: Individuals with epilepsy are at increased risk of ASD, especially if epilepsy appears in childhood. Further, ASD is more common in the siblings and offspring of individuals with epilepsy, suggesting shared etiology.